How can the ASICC learning model improve students' critical thinking skills on green/blue economy issues? - Santoso, Agus Muji; Primandiri, Poppy Rahmatika; Maulina, Dina; Zubaidah, Siti; Ibrahim, Nor Hasniza (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Learning that integrates the green/blue economy through the ASICC model has improved students' critical thinking skills. However, there was currently no scientific explanation for this case. Therefore, this study was aimed to reveal how the ASICC learning model can improve students' critical thinking skills. The case study was conducted in a class that implementing the ASICC learning model. Data of critical thinking skills was collected using a critical thinking test instrument integrated with essay test questions for conceptual understanding. Learning activity scores at each stage of the ASICC model are assessed using a rubric that has been developed. Multiple regression analysis was used to obtain contribution scores for each stage of student learning activities. This study revealed that the interpretation stage has the highest influence or contribution compared to other stages, namely reaching 51.71% towards increasing students' critical thinking scores. In order to improve students' critical thinking scores through the ASICC model integrated with green/blue economy issues, teachers should allocate sufficient time to students at the interpretation stage.